RANCANG BANGUN SISTEM INFORMASI MANAJEMEN GURU BERBASIS WEB STUDI KASUS PADA SMP N SATU ATAP LEREP UNGARAN BARAT (Information Technology and Telematics, 2013)
Seeing as the important role of teachers in the educational process as well as the parties responsible for the implementation of the education process in schools, teachers are required to have the skill, responsibility and spirit willing to give social service above personal interests. With the development of information and computing is rapidly increasing and the various facets of life, then eventually push SMP N One Roof Lerep West Ungaran to follow these developments in order to enhance the quality of its education system. For it is in the writing of this final report, the authors take the title "Design Build Master of Information Systems Management Web-Based Case Study at SMP N Satu Atap Lerep Ungaran Barat”. This study aims to apply the Master of Information Systems Management at SMP N Satu Atap Lerep Ungaran Barat model of web-based CMS (Content Management System) is a system that can create, manage, distribute, and publish, where the admin does not have to know HTML tag to run them. From this discussion of information systems generate SMP N Satu Atap Lerep Ungaran Barat web-based, which features: profile of the school, teacher data, sertifikasi.Berdasarkan terms of implementation and results of testing the system the authors hope this information the system can be fully utilized. Keywords: Teacher Management Information Systems, CMS